The Comparative of Speech Act Used in Indonesia and Japan Online News Media After The Earthquake Disaster - Helmita, Helmita (Jurnal Ilmiah Langue and Parole, 2025)
This study uses speech act theory, especially regarding comparative of speech act used in Indonesia and Japan online news media after the earthquake disaster. The purpose of writing these are to find the kind of speech acts used in Indonesia and Japan online news media,the classifying of speech acts used in Indonesia and Japan online news media and the metaphor of speech acts used in Indonesia and Japan online news media. This paper used Qualitative method. The technique used in this research is collecting the data. The research procedure included: finding data, classification data, and analyzing the result of data. The data is analyzing by collecting, selecting, and classifying the suitable utterances with the method. From the data above, many metaphors that can be found, beside that there are so many representatives that can be found from classifying of speech act. Locution, illocution and Perlocution also variated. Only one data from all of the data that can’t be found metaphors, that is from data 1. In data 1, researcher can’t found the metaphors, the researcher only found locution, illocution, perlocution and also classifying of speech act.